Local surface plasmon resonance of metallic nanoparticles embedded in amorphous silicon - Fantoni, Alessandro (2017)
This work reports a theoretical study aimed to identify the plasmonic resonance condition for a system formed by metallic nanoparticles embedded in an a-Si:H matrix. The study is based on a Tauc-Lorentz model for the electrical permittivity of a-Si:H and a Drude model for the metallic nanoparticles and the polarizability of an aluminium sphere shaped particle with radius of 10-20 nm. We also performed FDTD simulations of light propagation inside this structure reporting about the effects caused by a single nanosphere of aluminium, silver and, as a comparison, an ideally perfectly conductor. The simulation results show that it is possible to obtain a plasmonic resonance in the red part of the spectrum (600-650 nm) when 10-20 nm radius aluminium spheres are embedded into a-Si:H. (C) 2017 Portuguese Society of Materials (SPM). Published by Elsevier, S.L.U.